Keikutsertaan Tutor Dalam Meningkatkan Hasil Belajar Warga Belajar Paket C Dalam Mata Pelajaran Bahasa Inggris di SPNF SKB Kota Pariaman - Tiara Urmila; Irmawita Irmawita (Universitas Negeri Padang, 2022)
This study is conducted on the basis of the tutors' participation in the study of package c in the SPNF SKB city of Pariaman is conducted well research is projected to have the tutor participate in the teaching aspect of the package c in the SPNF SKB city of Pariaman, (3) measuring the placement of the tutor in the facilitator aspect of the facility's study of the package c at SPNF SKB city Pariaman, (4) depicts the tutor's participation to the evaluator aspect of the package c in SPNF SKB city Pariaman. This study includes a quantitative descriptive study that describes the data as it exists in a population of 53 people and a sample of 42 people are established by the stratification sample withdrawal technique random sampling. A data-collection device using angkets and documentaries. The data analysis USES the percentage formula. Research indicates that the tutor's participation in the increased learning result of the study of the c residents of the English subject was good, this is seen and the (1) the teacher aspect, (2) the motivational aspect, (3) the facilitator aspect, (4) the evaluator aspect. The suggestion that the tutor's contribution to the learning result can be further improved during the process of study.